Micrometeorological measurements over 3 years reveal differences in N 2 O emissions between annual and perennial crops - Diego Abalos; Shannon E. Brown; Andrew C. Vanderzaag; Robert J. Gordon; Kari E. Dunfield; Claudia Wagner‐Riddle (Global Change Biology, 2016)
Perennial crops can deliver a wide range of ecosystem services compared to annual crops. Some of these benefits are achieved by lengthening the growing season, which increases the period of crop water and nutrient uptake, pointing to a potential role for perennial systems to mitigate soil nitrous oxide (N 2 O) emissions. Employing a micrometeorological method, we tested this hypothesis in a 3‐year field experiment with a perennial grass‐legume mixture and an annual corn monoculture. Given that N 2 O emissions are strongly dependent on the method of fertilizer application, two manure application options commonly used by farmers for each crop were studied: injection vs. broadcast application for the perennial; fall vs. spring application for the annual. Across the 3 years, lower N 2 O emissions ( P 0.001) were measured for the perennial compared to the annual crop, even though annual N 2 O emissions increased tenfold for the perennial after ploughing. The percentage of N 2 O lost per unit of fertilizer applied was 3.7, 3.1 and 1.3 times higher for the annual for each consecutive year. Differences in soil organic matter due to the contrasting root systems of these crops are probably a major factor behind the N 2 O reduction. We found that a specific manure management practice can lead to increases or reductions in annual N 2 O emissions depending on environmental variables. The number of freeze‐thaw cycles during winter and the amount of rainfall after fertilization in spring were key factors. Therefore, general manure management recommendations should be avoided because interannual weather variability has the potential to determine if a specific practice is beneficial or detrimental. The lower N 2 O emissions of perennial crops deserve further research attention and must be considered in future land‐use decisions. Increasing the proportion of perennial crops in agricultural landscapes may provide an overlooked opportunity to regulate N 2 O emissions.